2014
DOI: 10.1371/journal.pone.0084132
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Novel Target for the Dysglycemic Chromogranin A Fragment Pancreastatin: Interaction with the Chaperone GRP78 to Influence Metabolism

Abstract: RationaleThe chromogranin A-derived peptide pancreastatin (PST) is a dysglycemic, counter-regulatory peptide for insulin action, especially in liver. Although previous evidence for a PST binding protein has been reported, such a receptor has not been identified or sequenced.Methods and ResultsWe used ligand affinity to purify the PST target, with biotinylated human PST (hCHGA273–301-amide) as “bait” and mouse liver homogenate as “prey”, and identified GRP78 (a.k.a. “78 kDa Glucose Regulated Protein”, HSPA5, BI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…We recently demonstrated the effectiveness of VER15008 as an inhibitor of HSP70 activity that interacts with its ATPase binding domain, although its specificity does not seem to exist exclusively for HSP70, but also for glucose‐related protein 78, another chaperone of the HSP family involved in the process of protein folding and glucose metabolism . Thus, the effects reported here might result from the inhibition of targets other than HSP70.…”
Section: Discussionmentioning
confidence: 86%
“…We recently demonstrated the effectiveness of VER15008 as an inhibitor of HSP70 activity that interacts with its ATPase binding domain, although its specificity does not seem to exist exclusively for HSP70, but also for glucose‐related protein 78, another chaperone of the HSP family involved in the process of protein folding and glucose metabolism . Thus, the effects reported here might result from the inhibition of targets other than HSP70.…”
Section: Discussionmentioning
confidence: 86%
“…A guanosine triphosphate (GTP)-binding protein-coupled receptor-mediated signaling pathway leading to activation of conventional DAG/Ca 2+ -dependent PKC and downregulation of mature Srebp-1c (p68) is thought to play a role in the anti-insulin effects of PST (11). Recently, we observed that PST could also modulate endoplasmic reticulum (ER) stress by interacting with binding immunoglobin protein (BiP)/78 kDa glucoseregulated protein (GRP78) (45). Feeding an HFD creates obesity, leading to hyperinsulinemia and inflammation (18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…37,38 Although high pancreastatin has been recognized as a feature of neuroendocrine tumors for some time, pancreastatin’s role in normal physiology remains poorly understood. 36,39 Pancreastatin seems to exert its effects through activity at membrane-associated G-proteins and phospholipase C, but a specific membrane-bound pancreastatin receptor (PSTR) has not been identified. 37,39 Attempts to identify the PSTR have focused on affinity purification from rodent liver.…”
Section: Discussionmentioning
confidence: 99%
“…36,39 Pancreastatin seems to exert its effects through activity at membrane-associated G-proteins and phospholipase C, but a specific membrane-bound pancreastatin receptor (PSTR) has not been identified. 37,39 Attempts to identify the PSTR have focused on affinity purification from rodent liver. 37,39 NETs overexpress many hormone receptors such as those for somatostatin and gastric-inhibitory polypeptide, 40-42 making it tempting to speculate that the putative PSTR might be more abundant in, and more readily isolated from, NET tissue specimens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation